O reino de Deus e as vítimas da história : uma abordagem segundo a cristologia de Jon Sobrino - Zanini, Rogério Luiz (2012)
This paper reflects about the theme: The Kingdom of God and the victims of history in the Christology of Jon Sobrino. We sought to verify the consistency of the relationship between the Kingdom of God and the victims of history. To answer this question we traveled, by biographical analysis, to the Author s theological thought. We did this in three chapters. In the first chapter the attention turns to the matrix that originated the sobriniano thought, with the central concern of understanding its theological proposal to overcome the victims suffering reality in the history. The second chapter seeks to understand how this theologian focuses on the Kingdom of God s category on his theology, and what is its originality. The third chapter seeks to point out the implications that the Kingdom of God demands in the work with the victims of history, as well as explain the degree of consistency between the Kingdom of God and the victims